Predatory activity of nematophagous fungi against Panagrellus redivivus in the soil under different plant species - Cardoso, Eliane R. [UNESP]; Nahas, Ely [UNESP] (Taylor & Francis, 2015)
The distribution of total and nematophagous fungi and nematodes is influenced by different plant species and environmental factors. The effect of moisture content and soil organic matter (SOM) in the frequency of fungi and nematodes was examined in Eutrustox soil with lettuce (Lactuca sativa), banana (Musa cavendishii), impatiens (Impatiens walleriana) and bahiagrass (Paspalum notatum). Total fungi and nematophagous counts were made in the rhizosphere soil (RS) and non-rhizosphere soil (NRS). The fungi were isolated from each soil, and their ability to predate Panagrellus redivivus nematode was evaluated. The fungi frequency in the RS and NRS ranged from 6.9 to 25.6 ï¿½ 105 and from 6.9 to 31.2 ï¿½ 105 CFU g-1 soil, respectively, and nematophagous fungi accounted for 21-34% and 16-33% of total fungi, respectively. The total and nematophagous fungi counts of RS decreased in the order lettuce>banana>bahiagrass>impatiens and lettuce>impatiens>banana>bahiagrass, respectively. Both total and nematophagous fungi counts from NRS decreased in the order lettuce>banana>bahiagrass>impatiens. A positive and significant correlation showed that fungi counts were influenced by the SOM and moisture contents. The abundance of nematodes was influenced by plant species, ranging from 0 to 4.0 ï¿½ 103 100 g-1 dry soil or roots. It can be concluded that the distribution of total and nematophagous fungi, and nematodes relates to plant species and the SOM and moisture contents.
Keywords: Lettuce; Nematode; Non-rhizosphere soil; Rhizosphere soil; Soil filamentous fungi